Effects of high‐mobility group box 1 on the proliferation and odontoblastic differentiation of human dental pulp cells. (19th April 2013) - Qi, S. C.; Cui, C.; Yan, Y. H.; Sun, G. H.; Zhu, S. R.
Abstract: Aim: To investigate the expression of high‐mobility group box 1 (HMGB1) in human dental pulp tissues and the effects of HMGB1 on proliferation and odontoblastic differentiation of human dental pulp cells (hDPCs). Methodology: Immunohistochemical assay, immunofluorescence staining and flow cytometric analysis were used to detect the expression of HMGB1 in the human dental pulp and hDPCs, respectively. The proliferation of hDPCs was examined by CCK‐8 after culturing human primary hDPCs in the presence of HMGB1 with different doses. Odontoblastic differentiation of hDPCs was determined using alkaline phosphatase (ALPase) activity assay and mineralized nodule formation. Important mineralization‐related genes such as ALP, dental sialophosphoprotein (DSPP) and dental matrix protein‐1 (DMP‐1) were determined by real‐time polymerase chain reaction. Western blot analysis was performed to determine the difference in expressions of DMP‐1 and DSP with or without the presence of exogenous HMGB1. Simultaneously, messenger RNA and protein levels of HMGB1 and RAGE were also detected. The protein level of HMGB1 in the supernatants was quantified using ELISA analysis. Results: HMGB1 was found in human dental pulp tissue and in the nuclei of hDPCs. During hDPC odontoblastic differentiation, HMGB1 translocated from the nuclei to the cytoplasm and then secreted out from hDPCs. Exogenous HMGB1 promoted hDPC proliferation and mineralized nodule formation. It up‐regulated the activity of ALPase and the mRNA and protein levels of dentine matrix protein‐1 (DMP‐1), alkaline phosphatase (ALP), dentine sialophosphoprotein (DSPP) and receptor for advance glycation end (RAGE) of hDPCs. Conclusion: HMGB1 promoted the proliferation and odontoblastic differentiation of hDPCs.